Soil quality and fertility dynamics under a continuous cassava-maize rotation in the semi-deciduous forest agro-ecological zone of Ghana - Adjei, Eric Owusu; Ayamba, Benedicta Essel; Buri, Mohammed Moro; Biney, Nathaniel; Appiah, Kwasi (Frontiers in Sustainable Food Systems, 2023)
The practice of crop rotation is known to significantly influence soil nutrient dynamics, depending on the type of rotation and the crops involved. As such, a field study was conducted to find out the effect of continuous cassava-maize rotation, where mineral fertilizer was only applied to the maize crop, on soil nutrients dynamics and soil quality thereof under varying rotation periods. The study revealed that Soil Organic Matter (SOM) and levels of soil nutrients, such as total nitrogen, available phosphorus and exchangeable cations (potassium, calcium, magnesium, and sodium) significantly declined with rotation period. Long term maize–cassava rotation led to subsoil (20–50cm) acidification. Soil quality as measured by Carbon Management Index (CMI) on the different aged rotations decreased with age, with the longest rotation period giving the least quality. These results and observations imply that long term cassava-maize rotation reduced soil quality and the resilience of the cropping system for continuous sustainable crops production. A regression analysis of soil nutrients with CMI under the continuous cassava-maize rotation identified the crucial role of soil total N (r2 = 0.56) and exchangeable K (r2 = 0.44) in sustaining productive cassava-maize rotation system and improved soil quality within the semi-deciduous forest agro-ecological zone. It is thus, recommended that enhanced and targeted organic and inorganic fertilization regime could be deployed on the cassava-maize rotation system to improve the inherently low levels of nutrients and increase crop yields.